Suppression of H2O absorption by hydrophobic-like surface of SiOx without Si-OH group - Ueda, Tetsuya; Kiso, Osamu; Abe, Shoji; Takezawa, Yasunari; Matsumaro, Kazuyuki; Suzuki, Chikashi; Toyama, Munehiro; Ogawa, Shinichi (Proceedings of the IEEE International Interconnect Technology Conference, 2020)
A mechanism of H 2 O absorption into SiO x films for forming hydrophobic surfaces is experimentally studied with annealing at several temperatures followed by exposure to several environment conditions. A key requisite to suppress H 2 O absorption was found to be a hydrophobic-like surface of SiO x , which was formed by annealing above 700°C, which completely removes the Si-OH group. This result indicates the possibility to fabricate the completed SiO x films that almost prevent H 2 O absorption regardless of the air exposure time periods.